Association of Transition Zone Burden With Recurrence in Elderly Patients With Paroxysmal Atrial Fibrillation Without Low‐Voltage Areas - Yuxuan Wang; Yue Qiu; Haojun Wang; Chang Cui; Zidun Wang; Xiaohong Jiang; Mingfang Li; Juejin Wang; Hongwu Chen; Minglong Chen (Clinical Cardiology, 2026)
ABSTRACT Background Transition zone (TZ) may serve as a potential substrate for atrial fibrillation (AF). This study aims to investigate the relationship of TZ burden with left atrial conduction velocity (LACV) and recurrence after circumferential pulmonary vein isolation (CPVI) in elderly patients with paroxysmal AF without low‐voltage areas (LVA). Methods Patients with paroxysmal AF without LVA were categorized into three groups based on the TZ burden (< 5%, 5%–15% and > 15%). TZs were defined as regions with bipolar voltage between 0.5 and 1 mV in more than 3 adjacent points. TZ burden was calculated as the proportion of TZ on the entire left atrium surface. LACV were calculated as conduction distance divided by conduction time. Recurrence was defined as any episode of atrial tachyarrhythmia (ATA) lasting ≥ 30 s after a 3‐month blanking period. Results Among the 158 enrolled patients (mean age 69.7 ± 3.8 years), 48 (30.4%) had a TZ < 5%, 66 (41.8%) had a TZ of 5%–15%, and 44 (27.8%) had a TZ > 15%. Patients with higher TZ burden exhibited significantly decreased anterior LACV (1.52 ± 0.36 vs. 1.21 ± 0.27 vs. 1.02 ± 0.25 m/s, p < 0.0001). After a mean follow‐up of 24.9 months, 40 (25.3%) patients experienced recurrence. Patients with recurrence had higher TZ burden (15.4 [7.2–22.4] vs. 8.2 [3.5–14.3], p < 0.0001). TZ burden remained significantly associated with recurrence in a multivariable Cox regression model (adjusted HR 1.065 [95% CI 1.034–1.098], p < 0.0001). Conclusions TZ burden is correlated with slow LACV and independently predicts ATA recurrence following CPVI.